WHY DO STUDENTS USE CHATGPT AND WHY DOES IT MATTER? Reflecting on the use of AI in higher education - Nebieridze, Mariam; Jojua, Nino (Online Journal of Humanities ETAGTSU, 2024)
Today, the educational discourse is closely tied to the concept of technological advancement that the 21st century is commonly associated with. The application of different types of online resources, virtual campus, , etc in the teaching-learning process by both educators and students has become an inseparable part of the global educational space that strives to maximally make the most of the technology to keep up with the fast-changing requirements of the modern labor market. The most recent AI generated technology, ChatGPT has been rapidly gaining popularity among students of different Higher Educational institutions in different parts of the world, and they report having used the tool for multiple purposes while studying (Appleby, 2023).Against this background, it is also vital to look deeper into the real-time context in Georgia and investigate the students’ perspectives and rationale for using it on the other side of the spectrum. Therefore, this paper reports and explores the study conducted among 74 undergraduate students of Ivane Javakhishvili Tbilisi State University, Georgia, to investigate their practice of using ChatGPT in the educational process between 2022 and 2024 to customize their learning experiences. The research findings will provide educators with useful food for thought at its initial stage to assist the compliance of the educational system with the newly emerged technological challenges such as ChatGPT and its adjustment to new teacher-learner needs. Full Text (PDF)